Strategy For Participatory Supervision of The Election Supervisory Agency In The Election of Regional Head of Kotabaru Regency In 2020 - Andi Muhammad Saidi; Ahmad Yunani; Andi Tenri Sompa (Wadah Inovasi Indonesia, 2022)
The purpose of this study was to analyze the participatory supervision strategy of the Kotabaru Regency Bawaslu together with the community in supervising the stages of the 2020 Direct Regional Head Election Campaign in the Kotabaru Regency. In addition, this study also analyzes the obstacles faced by the Kotabaru Regency Bawaslu and the community in the 2020 simultaneous direct regional head elections in Kotabaru Regency. The approach in this study is qualitative. This approach is used to obtain clear and factual descriptions and information regarding the participatory supervision of the Kotabaru Regency Bawaslu in the 2020 Kotabaru Regency Head election. In general, the strategy that has been implemented by the Kotabaru Regency Bawaslu is quite effective. It's just that the focus of the strategy and participatory monitoring efforts that were initiated only focused on a handful of issues and the targeted community. Participatory monitoring strategies such as the Online Reporting Strategy (SIWASLU Application), Online Reporting Strategy (Google Form), Citizen Forum Initiation, and Monitoring Corner are still very limited in scope. The use of this method is quite effective during a pandemic like this, to continue to comply with health protocols and maintain distance and crowds. The obstacle in participatory supervision faced by Bawaslu in the 2020 Simultaneous direct regional head elections in Kotabaru Regency is the neutrality of ASN where this problem is very prone to the occurrence of ASN Neutrality, such as in the education sector, around the Civil Servant's office, and District offices, and offices. -District Office. The second obstacle is Money Politics. In terms of legal aspects and law enforcement institutions, there are still many gaps. Regulations concerning the prohibition of money politics are not rigidly regulated in the law because they depend on the interests of the regulators themselves. The next obstacle is the politicization of identity politics issues